Social prescribing for patients of secondary mental health services: emotional, psychological and social well-being outcomes. Issue 4 (30th March 2020) - Dayson, Chris; Painter, Jo; Bennett, Ellen
Abstract : Purpose: This paper aims to identify the well-being outcomes of a social prescribing model set within a secondary mental health service recovery pathway and understand the key characteristics of a social prescribing referral for producing these outcomes. Design/methodology/approach: A qualitative case study of one mental health social prescribing service with three nested case studies of social prescribing providers. Semi-structured interviews were undertaken with commissioners, providers and patients (n = 20) and analysed thematically. Findings: Social prescribing makes a positive contribution to emotional, psychological and social well-being for patients of secondary mental health services. A key enabling mechanism of the social prescribing model was the supportive discharge pathway which provided opportunities for sustained engagement in community activities, including participation in peer-to-peer support networks and volunteering. Research limitations/implications: More in-depth research is required to fully understand when, for whom and in what circumstances social prescribing is effective for patients of secondary mental health services. Practical implications: A supported social prescribing referral, embedded within a recovery focussed secondary mental health service pathway, offers a valuable accompaniment to traditional approaches. Current social prescribing policy is focussed on increasing the number of link workers in primary care, but this study highlights the importance models embedded within secondary care and of funding VCSE organisations to receive referrals and provide pathways for long-term engagement, enabling positive outcomes to be sustained. Originality/value: Social prescribing is widely advocated in policy and practice but there are few examples of social prescribing models having been developed in secondary mental health services, and no published academic studies that everybody are aware of.